Widzialny symbol wiary. Motyw ikony w twórczości literackiej Fiodora Dostojewskiego - Walczak, Dorota (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The present work is devoted to the analysis of the icon motif in the works of F. M Dostoyevsky (1821 – 1881). The author of this paper tries to prove her own thesis that the famous writer’s opinion of his literary characters depended distinctly on their attitude towards icons. In this paper Dostoevsky's books such as The Landlady, Netochka Nezvanova, Demons, The Adolescent, The Meek One and The Brothers Karamazov are analyzed.